Physiological role of alpha-melanocyte-stimulating hormone in modulating the secretion of prolactin and luteinizing hormone in the female rat. - Khorram, O (1984)
Long-term ovariectomized (OVX) rats were injected in the third cerebral ventricle with 5 microliter of the globulin fraction of an antiserum raised against alpha-melanocyte-stimulating hormone (alpha-MSH) or an equal volume of the globulin fraction of normal rabbit serum (NRS). Immunoneutralization of brain alpha-MSH produced an increase in the area under the secretion curve of prolactin (Prl), the amplitude of Prl pulses, and mean plasma Prl (P less than 0.01). In animals that had received two injections of NRS or anti-MSH and were subjected to a 2-min ether stress, Prl levels significantly increased within 5 minutes in the NRS-injected rats, whereas Prl levels in the antiserum-injected rats did not increase any further from the initially high baseline levels. The administration of antibodies against alpha-MSH produced a small increase (P less than 0.05) in the area under the secretion of luteinizing hormone (LH) and mean plasma LH; however, the number of LH pulses was unaffected. We conclude that endogenous alpha-MSH of central origin is a physiological neuromodulator of release of Prl and LH in the OVX rat and is involved in the stress-induced release of Prl.